Inhibitory Effect of Acetylsalicylic Acid on Human Platelet Function in Normal Volunteers and in Women Using a Combined Oral Contraceptive Regime - Baele, G; Thiery, M; Vermeulen, A; Barbier, F (Thrombosis and Haemostasis, 1976)
Six parameters related to the release reaction were measured simultaneously in 10 human volunteers prior to the intake of one single dose of 1 g acetylsalicylic acid and 1, 4, 5, 6 and 7 days later: ΔE5 with diluted collagen, ΔE10 with Thrombofax® and the serotonin-14C release by undiluted and diluted collagen, by Thrombofax and by bovine plasma. The duration of the inhibitory effect varied according to the test used. It was the most prolonged (through the 7th day) if serotonin-14C release by diluted collagen was measured.A systematic investigation of the platelet release reaction in women taking a combined oral contraceptive was also performed. There were no statistically significant differences from a control group. No difference in acetylsalicylic acid sensitivity, measured 24 hours after intake of 1 g of aspirin, could be demonstrated.